Working at home in the ancient Near East - Mas, Juliette,; Notizia, Palmiro, 1980- (Archaeopress ancient Near Eastern archaeology ;, 2020)
'Working at Home in the Ancient Near East' brings together the papers and discussions from an international workshop organised within the framework of the 10th International Congress on the Archaeology of the Ancient Near East held in Vienna in April 2016. It examines the organisation, scale, and the socio-economic role played by institutional and non-institutional households, as well as the social use of domestic spaces in Bronze Age Mesopotamia. The invited speakers - archaeologists, philologists, and historians specialising in ancient Mesopotamia - who approached these topics from different perspectives and by analysing different datasets were encouraged to exchange their views and to discuss methodological concerns and common problems.